CONTACT FATIGUE LIFE ANALYSIS OF WHEEL EDGE REDUCER GEAR OF DRIVE AXLE OF LOADER BASED ON LOAD SPECTRUM (MT) - YANG SiYuan; SONG XuDing; ZHANG Lei (Jixie qiangdu)
In view of the contact fatigue problem of the wheel side reducer gear of the drive axle of the loader during its service, the fatigue life was evaluated. Finite element models of the sun wheel and the planet wheel were established in Hypermesh. Statics and transient dynamics were solved in Ansys Workbench according to the fatigue loading spectrum. The fatigue life was calculated in Ncode environment based on statics and transient dynamics. The fatigue life calculated based on finite element was compared with the bench test results. The results show that the contact stress calculated by transient dynamics is greater than that calculated by static. The fatigue life based on transient dynamics is 47 417 h, which is closer to the experimental results, and the relative errors are 9.32% and 15.14%. The analysis results provide reference and basis for the optimization and fatigue life evaluation of the drive axle gear system of loader.